School Directors of Rio de Janeiro and its Relationship with Democratic Management: an experience of Specialization in School Management (Escola de Gestores) UFF / SEB / MEC (Research, Society and Development, 2018)
The law 13.0005 / 2014 establishes the National Education Plan (PNE). Among the set of goals that give substance to this Plan stands out the number 19, which regulates the establishment of Democratic Management in Schools. In view of this goal and the strategies involved, we propose to discuss the relationship between Democratic Management and the (possible) construction of a National Education System using as an empirical instance the experience obtained at the Specialization Course in School Management UFF / SEB / MEC (Escola de Gestores) regarding the formation of directors responsible for municipal schools Thus, we discuss the possible relations between local and national in the implementation of a National Education System managed based on the assumptions of Democratic Management. At the end of the study it was possible to verify that Democratic Management is not yet fully effective in schools due to questions regarding the training of managers, as well as the objective conditions of development of their administrative routines.